Analysis of Health Behavior of Adolescents in Tuban, Indonesia - Titik Sumiatin; Wahyu Tri Ningsih; Su’udi; Aby Yazid Al Busthomy Rofi’i; Roudlotul Jannah; Siti Kotijah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Adolescence is a period associated with increased risk behaviors such as smoking, sex, fighting, the use ofsharp weapons and so on. These conditions coincide with changes in social and school environment. Thepurpose of this study is to explain how health risk behaviors are to adolescents. The research design usedin this study was analytic with a cross sectional approach. The population was all high school/vocationalschool adolescents with a total of 29,963 boys and girls, with a sample size of 395 using cluster samplingtechnique. The independent variable of the study is risk behavior and the dependent variables of the studyare smoking, bullying, use of sharp weapons, driving, drug consumption, sex, health consultation, nutritionalfulfillment, suicide attempt, alcohol consumption, fighting and physical activity. Data collection was carriedout using a questionnaire adopted from YRBSS (Youth Risk Behavior Surveillance System) which wastranslated into Indonesian. The collected data was tabulated and analyzed using Logistic Regression. Theresults showed that all health behavior including risk behaviors, although based on statistical test resultsthe behavior of alcohol and drug consumption was not significant because (p value) was 0.000>0.005.Smoking behavior had a regression coefficient of 6,904 with a significance level (p value) of 0.000<0.005and an OR (odds ratio) of 996,365, which means that adolescents have 996 times the chance to smoke. Allvariables are included in health risk behaviors; however, smoking is the riskiest health behavior carried outby adolescents